SEPARATION AXIOMS ON MULTISET TOPOLOGICAL SPACE - Sobhy El-sheikh; Rajab Omar; Mahmoud Raafat (Journal of New Theory)
− The aim of this paper is to introduce separation axioms on multiset topological spacesand study some of their properties. Characterization of these spaces and some examples haveinvestigated. Furthermore, we show that such separation axioms are preserved under hereditaryproperties